Bioenergy: Pointing To The Future - Conway, Roger K.; Erbach, Don; Duncan, Marvin; Gallagher, Paul; Shane, Philip L.; Smith, Peter F.; Tumbleson, M. E. (Council for Agricultural Science and Technology (CAST), 2004)
Composed of five stand-alone pieces, this issue paper highlights the current science, processes, and potentials for energy production through agriculture, and outlines future research needs. Among the topics addressed in this introduction to the subject of bioenergy are the economics and rural development of bioenergy, environmental and natural resource effects, technology and research, and the need for a systems approach. Public policy considerations such as long-term societal issues and acceptable risk also are discussed.